Implications of carbon pricing on food affordability and agri-food sector in Canada: A scoping review - Sylvain Charlebois; Swati Saxena; Gumataw Abebe; Tony Walker; Janet Music; Vlado Keselj; Karim Tuffaha; Keshava Pallavi Gone; Janele Vezeau; Bibhuti Sarker; Stacey Taylor (Transportation Research Interdisciplinary Perspectives, 2024)
This review delves into the effects of carbon pricing policies on food affordability and the performance of the agri-food sector, with a specific focus on Canada. Against the backdrop of the widespread adoption of carbon pricing as a crucial tool in reducing greenhouse gas (GHG) emissions, the discussion acknowledges potential economic repercussions, particularly for lower-income households. Findings reveal that the implementation of a mandated carbon tax across all provinces in Canada by 2019 led to reduced GHG emissions and an increase in food prices. In addition, this review positions Canada within the global context by examining actions taken by other countries and their impacts. Crucial research gaps are also identified, ultimately serving as a guide for future studies and policy formulation aimed at balancing the necessity of carbon tax implementation with considerations of food affordability.